Telaah Pelaksanaan Sosialisasi Rancangan Peraturan Daerah dan Peraturan Daerah oleh DPRD Provinsi Kalimantan Tengah - Sandi, Jhon Retei Alfri; Satriawan, Bismar Harris (Jurnal Pemerintahan dan Politik, 2024)
Background: The authority of DPRD to carry out the socialization of local regulations (Perda) through the allocation- absorption of the local regulation socialization budget (sosper) in the secretariat of certain DPRDs has become a polemic today. This study explains the implementation of dissemination or socialization of draft local regulations (Raperda) and local regulations (Perda) can be done in the legislative function of DPRD. Research findings using a qualitative approach through a literature review of laws and regulations and documentation data collection techniques show that: (i) the implementation of dissemination or socialization of draft regulations and local regulations can be done comprehensively. This is an integral part of the function and authority of the DPRD as a legislative body that has the responsibility and authority to form local regulations, especially those proposed as DPRD initiatives. (ii) The implementation of dissemination or socialization of local regulations can be carried out as long as there is a legal basis governing its implementation, such as local regulations, gubernatorial regulations, DPRD regulations and included in the main points of thought (Pokir) of DPRD, RKPD, KUA-PPAS and carried out in accordance with applicable mechanisms and procedures. (iii) The involvement of the DPRD in the dissemination or socialization of draft regulations and local regulations is a form of optimization of the functions and authority of the legislative body in forming local regulations. The creation of good, aspirational and representative local regulations that reflect the interests of the community.